Surgical importance of distance from mandibular condyle to carotid canal and foramen spinosum: an anatomical study - Arumugam, Sangeetha; Subbiah, Nandha Kumar (International Journal of Research in Medical Sciences, 2019)
Background: The objective of this study was to compare the distance from mandibular condyle to internal carotid artery and middle meningeal artery. Methods: In this study 20 skulls obtained from the Department of Anatomy were utilized for the study. The following two parameters were measured using Vernier Caliper (digital). 1. Distance from Mandibular condyle to carotid canal 2. Distance from medial margin of Mandibular condyle to Foramen spinosum. All the measurements were taken thrice to minimize errors. Photograph of the skull base showing the measurements done was captured. Results: A total of 40 sides, 20 right and 20 left sides were studied. The mean distance between medial margin of mandibular condyle to carotid canal was 11.2 mm±0.6 on right side and 11.6mm±0.8 on left side. The mean distance from the medial margin of mandibular condyle to Foramen spinosum (middle meningeal artery) was 9.3 mm±1.1 on right side and 9.8mm±0.9 on left side. Conclusions: The distance between mandibular condyle to Middle meningeal artery is less compared to the distance between Mandibular condyle to carotid artery. The current study concludes that MMA is comparatively at high risk for damage compared to internal carotid artery.